Profile of Pesantren Students’ Character, Scientific Reasoning Skills and Its’ Relationship - Maria Chandra Sutarja; Badrud Tamam; Enny Nur Andryani; Imas Hari Iswanto (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2022)
Pesantren is an institution that focuses on students’ character building. Students have to stay 24 hours in Pesantren to participate in character building conducted by Pesantren. Many people trust to educate their children in Pesantren. Due to people’s trust in Pesantren and 21st century skills that should be conquered, the research was conducted to identify students’ character, scientific reasoning skills, and its’relationship. Result of the research could be the base to develop learning system, instruction, and media. The research was conducted in a survey method, using the LCTSR version of 2000 and character self- assessment. It was conducted in one of Pesantren in Pamekasan. 56 students was participated as the sample of the research. Learning instruction and character building in Pesantren were also described. The result shows that students in Pesantren have hard work character as the highest character scorescore and honesty as the lowest character scorescore. It indicates that Pesantren needs to reform character building program, especially to build honesty. Students’ scientific reasoning skills are low. More than 98% are at a concrete level of cognitive development and there is no correlation between students’ character and scientific reasoning skills. Due to the result, there should be a transformation in the learning system in Pesantren, to improve students’ scientific reasoning skills.